Picking the right surgeon: Quantitative approach - Suhir, E (Global Journal of Medical and Clinical Case Reports, 2021)
There is an abundance of useful verbal information and recommendations on how to make the best choice when referring a patient for surgery or when seeking the right surgeon for your own operation. A quantitative approach is suggested here on how this could be done through assessing the probability of success and/or the Mean-Time-To-Failure (MTTF) of the planned operation by considering and comparing the skills of two highly qualified candidates. Then the chooser could continue this effort by comparing the background and the probability of success of the best one of these two candidates with the next suitable candidate, and then go on with the process for as many candidates as he/she would like to evaluate. The approach suggests using the double-exponential highly flexible and highly physically meaningful probability Distribution Function (DEPDF) as a suitable model. This function was introduced about a decade ago in the reliability physics to quantify, on the probabilistic basis, the outcome of a particular engineering, ergonomics or medical undertaking of importance. The surgeon’s qualifications are identified in our approach as Human Capacity Factor (HCF). Figures of Merit (FoM) of this factor consider many relevant human qualities, as well as the durations and the outcomes of the surgeon’s previous, both successful and failed, operations. The mental (cognitive) workload (MWL) reflects the complexity of the operation and, in the present analysis, is assumed to be the same for the two surgeon’s considered. The role of an anesthesiologist is not taken into account directly in our approach: it is the surgeon who decides on his/hers partner, and the surgeon’s choice is viewed as part of his/hers HCF. The general concepts are illustrated by a numerical example.